Depth-age model of the B21_2012 firn core - Freitag, Johannes; Kipfstuhl, Sepp; Weißbach, Stefanie; Karlsson, Nanna Bjørnholt; Münch, Thomas; Hörhold, Maria (In: Freitag, J et al. (2021): Extension of the stable oxygen isotope and density profile of the ngt27C94.2 (B21) firn core [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.931744, 2021)
Using raw, un-calibrated dielectrical profiling (DEP) data from the field (NEEM Set-up), volcanic tie points were derived. Together with the smoothed density data and the isotopic composition the record was dated by layer counting.
Keywords: firn core; North Greenland Traverse